The Selfless Love and Human Needs. - Strzyżyński, Przemysław Aleksander (Filozofia Chrześcijańska, 2014)
In my article I present two concepts of love. One is developed by Anders Nygren, and it rejects any human needs from the space of love. The second tries to defend human needs as an important background of human relations. My own thesis underlines the possibility of understanding love as accepting human needs. I am defending the vision of human nature which includes needs, like sense of security, acceptance, freedom, autonomy or sense of life. On this ground I try to show that human fundamental needs are conditions of love.